Postcards from somewhere: 'marginal' cultural production, creativity and community - Mayes, Robyn (Routledge, 2011)
This paper focuses on a case study of local postcard production in a rural community in Western Australia. Drawing on in-depth interviews with key producers of these postcards, the analysis presented explores perceptions of and contexts for the emergence of this production, in turn examining the notion of ‘creativity’ articulated and privileged by this cultural work. Connections are identified between the making of postcards, the broader historical field of local cultural work and the construction of community. This, in turn, forms the basis for consideration of the role and relativity of ‘marginality’.